Incidental diagnosis of a spindle cell type gastrointestinal stromal tumor in a dog with ethylene glycol intoxication - Serpa, Priscila B S (Veterinary clinical pathology, 2022)
© 2021 American Society for Veterinary Clinical Pathology.